1982
DOI: 10.1002/j.1552-4604.1982.tb02164.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Hydroxyethyl Starch in Normal Subjects

Abstract: To determine the elimination of high-molecular-weight hydroxyethyl starch (HES, Mw 450,000) in normal subjects, ten volunteers were given 500 ml 6% HES solution by intravenous infusion, and serial blood and urine samples were collected for nonglucose total carbohydrate determination. On the average, 46 and 64 per cent of the dose was excreted in the urine within two and eight days, respectively. The plasma concentration declined rapidly during the first week after infusion. The average terminal half-life was 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

1983
1983
2016
2016

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(35 citation statements)
references
References 8 publications
3
32
0
Order By: Relevance
“…Using an assay that measures reducing sugars formed by amylase action" rather than disappearance of an added substrate.v:" it was shown that the urinary level of ex-amylase is not decreased, but in reality, slightly increased. 34 These data suggested the possibility of another mechanism, perhaps as simple as an increased release of ex-amylase from various tissues, as a result of the presence of HES in the body.…”
Section: Leukapheresis a Seco Nd Frequent Use Of Hetastarchmentioning
confidence: 96%
See 2 more Smart Citations
“…Using an assay that measures reducing sugars formed by amylase action" rather than disappearance of an added substrate.v:" it was shown that the urinary level of ex-amylase is not decreased, but in reality, slightly increased. 34 These data suggested the possibility of another mechanism, perhaps as simple as an increased release of ex-amylase from various tissues, as a result of the presence of HES in the body.…”
Section: Leukapheresis a Seco Nd Frequent Use Of Hetastarchmentioning
confidence: 96%
“…12 Figure 2 depicts typical average plasma concentrations and urinary excretion rate vs. time profiles in normal subjects after infusion of hetastarch 6070 500 ml. 34 In man, the urinary excretion is very rapid both during and immediately after infusion, with elimination rates of 2.19 and 2.34 g/h, respectively. :"':" This rate decreases with time to 1.40, 0.40, 0.15, and 0.08 g/h at 2 to 4-, 4 to 8-, 12 to 24-, and 24 to 48-hour urinary collection periods, respectively.…”
Section: Dispositionmentioning
confidence: 99%
See 1 more Smart Citation
“…The average terminal half-life is 17 days. Plasma volume expansion persists for at least 48 hours, 36 with 40% of the peak effect persisting after 24 hours. Hetastarch produces a significantly greater increase in plasma COP compared with an equal volume of 5% albumin.…”
Section: Hydroxyethyl Starchesmentioning
confidence: 95%
“…Studies on the pharmacokinetics of hydroxyethyl starch in humans have been performed with faeces 6 and with urine 7 using trimethylsilyl (TMS) derivatives derived from HES. The methylation of carbohydrates and further derivatization to partially methylated alditol acetates (PMAAs) is a common method in sugar analysis 8 -12 to obtain unambiguous information regarding the position of linkages and to determine the extent of branching.…”
Section: Introductionmentioning
confidence: 99%